2022
DOI: 10.1101/2022.10.04.510829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of visual pollution on navigation mechanisms in the damselfish (Chrysiptera cyanea)

Abstract: Here, we investigate whether visual pollution has an effect on navigation in coral reef damselfish (Chrysiptera cyanea). Turbidity had no significant influence on the individual fish's preference between egocentric and visual cues in a simple navigation task, with all individuals exhibiting a striking egocentric preference across all turbidity levels under testing. However, an alteration of cue preference may have occurred on a fine scale. Turbidity had profound effects on fish movement and decision-making beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Odling-Smee [ 20 ] similarly found that sticklebacks from pond habitats favored landmarks, though those from river habitats were more likely to use egocentric cues. In contrast, damselfish strongly favored egocentric rather than visual cues in a range of turbidities, surprisingly including in clear water [ 21 ]. Regarding differences between axes, both banded tetras and bronze Corydoras ( C. aeneus ) have been shown to prefer vertical information and disregard visual landmarks and horizontal information, respectively, in Y-maze tasks [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Odling-Smee [ 20 ] similarly found that sticklebacks from pond habitats favored landmarks, though those from river habitats were more likely to use egocentric cues. In contrast, damselfish strongly favored egocentric rather than visual cues in a range of turbidities, surprisingly including in clear water [ 21 ]. Regarding differences between axes, both banded tetras and bronze Corydoras ( C. aeneus ) have been shown to prefer vertical information and disregard visual landmarks and horizontal information, respectively, in Y-maze tasks [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%